Ovarian cancer: new strategies and emerging targets for the treatment of patients with advanced disease. Issue 2 (1st February 2021) - Arend, Rebecca C.; Jackson-Fisher, Amy; Jacobs, Ira A.; Chou, Jeffrey; Monk, Bradley J.
ABSTRACT: Recently approved therapies have contributed to a significant progress in the management of ovarian cancer; yet, more options are needed to further improve outcomes in patients with advanced disease. Here we review the rationale and ongoing clinical trials of novel combination strategies involving chemotherapy, poly ADP ribose polymerase, programmed death 1 (PD-1)/PD-ligand 1 immune checkpoint and/or vascular endothelial growth factor receptor inhibitors. Further, we discuss novel agents aimed at targets associated with ovarian cancer growth or progression that are emerging as potential new treatment approaches. Among them, agents targeted to folate receptor α, tissue factor, and protein kinase-mediated pathways (WEE1 kinase, phosphatidylinositol-3 kinase α, cell cycle checkpoint kinase 1/2, ATR kinase) are currently in clinical development as mono- or combination therapies. If successful, findings from these extensive development efforts may further transform treatment of patients with advanced ovarian cancer.